Advances in ultrafast gas-phase x-ray scattering. (11th November 2020) - Stankus, Brian; Yong, Haiwang; Ruddock, Jennifer; Ma, Lingyu; Carrascosa, Andres Moreno; Goff, Nathan; Boutet, Sébastien; Xu, Xuan; Zotev, Nikola; Kirrander, Adam; Minitti, Michael P; Weber, Peter M
Abstract: Recent developments of x-ray free electron lasers and pulsed electron sources have enabled ultrafast scattering to become an increasingly powerful tool for exploring molecular dynamics. This article describes our recent experimental and methodological advances in ultrafast gas-phase x-ray scattering experiments at the LCLS. A re-designed short-pathlength windowless diffractometer is coupled with careful optimization of sample density and independent normalization of x-ray intensity fluctuations to provide gas-phase scattering patterns with exceptionally high signal-to-noise ratios. These advances, coupled with careful geometry optimization and data treatment, provide both ground- and excited-state signals in excellent agreement with high level ab initio total scattering patterns.